Sosialisasi Dan Pendampingan Aparatur Desa Dalam Manajemen Tata Kelola Pemerintahan Desa Tublopo, Nusa Tenggara Timur - Piki Darma Kristian Pardede; Dimas Agustian; Sri Miranti Mamida; Pedro Des Kellen Usnaat; Melita Yolanda Bani (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
The village holds a strategic role as the spearhead of national development in realizing community welfare through the independent management of local potential. However, many villages in Indonesia, including Tublopo Village in North Central Timor Regency, still face limitations in the capacity of village apparatus, low community participation, and suboptimal systems for recording village potential. This Community Service Program (PKM) was conducted by the university as an implementation of the Tri Dharma of Higher Education with the aim of strengthening village governance and enhancing community empowerment. The methods employed included socialization, technical assistance, and the Participatory Rural Appraisal (PRA) approach, which emphasizes active community participation. The results of the program indicate a significant improvement in the apparatus’ understanding of Village Fund governance, increased government transparency, and greater community participation in cleanliness activities and local potential data collection. Another outcome of this activity was the compilation of the 2025 Tublopo Village Potential Profile based on accurate data, which serves as a foundation for evidence-based development planning. This program demonstrates the strategic role of higher education institutions in supporting transparent, participatory, and accountable village governance, as well as in fostering an independent and empowered community.